Quality of life and alaryngeal communication methods: a scoping review (Research, Society and Development, 2022)
Objective: To present a mapping of studies involving the quality of life of the total laryngectomees regarding the laryngeal communication methods and instruments used. Method: The question to be answered is: “Which instruments, validated and psychometrically reliable, are used to assess the quality of life-related to laryngeal communication in total laryngectomees?”. To answer this question, the following eligibility criteria were defined, according to the acronym: P- Population - Total laryngectomy patients, C- Concept - Another form of laryngeal communication, C- Context- Quality of life after total laryngectomy. After defining the eligibility criteria, consult the databases with the DeCS/MeSH and Emtree descriptors: “Laryngectomy, Quality of Life, Speech, Alaryngeal”, combined with the Boolean operator “AND” and for Portuguese, English, and Portuguese. Spanish. Results: 238 scientific texts were obtained, 4 articles in Lilacs, 74 in PubMed, 21 in Embase, 92 in Scopus, 42 in Web of Science, zero (0) in OpenGrey, two (2) in Google Scholar, and three (3) at the BDTD (Brazilian Digital Library of Theses and Dissertations). Conclusion: The instruments most used to assess the quality of life in total laryngectomees are: Quality of Life in Voice (QVV), followed by the University of Washington Quality of Life Questionnaire (UW-QOL), and the EORTC Quality of Life Questionnaire protocols ( EORTC QLQ-C30), the University of Michigan Head And Neck Quality of Life Instrument (HNQOL), Quality of Life Questionnaire -SF-36.